Status and Threats to Fish Diversity and Water Quality of Semariang Mangrove Area, Sarawak, Malaysia - Lee, Nyanti; Roslan, Nur 'Asikin; Ling, Teck Yee; Grinang, Jongkar (Universiti Malaysia Sarawak, 2013)
This study aimed to document the status and threats to the fish diversity and water quality at Sungai Semariang mangrove area, which is located on the eastern part of Kuching Wetland National Park. A total of 32 families represented by 76 species of fish were caught from the area. The six dominant families in terms of the number of individuals caught were Ariidae (35 percent), Sciaenidae (11 percent), Engraulidae (9 percent), Leiognathidae, Mugilidae and Pristigasteridae (7 percent each). The four families with the most number of species were Sciaenidae (12 species), Ariidae (10 species), Engraulidae (6 species) and Leiognathidae (5 species), Arius venosus was the most common species with the highest number of individuals caught. Most of the individuals caught from the area were small sized individuals indicating the importance of the area as nursery, feeding, breeding and shelter areas for many species of fish. Water temperature ranged from 28.0 to 30.2 °c and pH from 6.9 to 7.3. Dissolved oxygen ranged from 2.4 to 3.8 mg/L. Low dissolved oxygen was found near flood mitigation works and downstream of residential areas. Among the threats to the area are residential areas and flood mitigation works.